Proposta de sequência didática para intervenção nos desvios ortográficos de verbos do pretérito perfeito do indicativo - Carvalho, Márcia dos Santos (2019)
The mastery of orthographic norms is a determining factor for the development of the writing skill, contributing to the clarity and understanding of ideas. Thus, we need a more systematic and reflexive teaching that aims at the development of a learner capable of perceiving the importance of the proper use of the orthographic rules in their daily life. Therefore, this research sought to analyze the applicability of a sequence of activities three related to regular morphosyntactic correspondences, more specifically, the replacement of the grapheme by <l> (for example, correu by correl) and <am> by <ão> (for example, correram for correrão) in the third person of verbs in the simple past. The investigation involved 48 students from two groups of the 6th year, experimental and control, of a public school in Fortaleza. During the process, strategies were presented, based on the conception of Vygotsky's socio-interactionist teaching, aiming at the accomplishment of previous activities, with the concept of the teacher as mediator and the student as an active subject of his/her learning. In addition, the work was based on Roberto's phonological processes (2016) and his contribution to overcoming specific difficulties of students regarding spelling. Regarding its nature, this research was based on action research, which is based on an action or collective problem in which researchers and participants engage in a participatory and collaborative manner. Using the spiral process of action research presented by Lewuin (1946), this study identified, through spontaneous writing and dictation, the main difficulties of the participants related to orthography. Based on this observation, actions were planned, which aimed to overcome the difficulties encountered, always considering that the evaluations of each phase could evoke possible changes in the following actions. After the interventions with the sequence of activities, two post-tests similar to the diagnosis ones were applied. Post-tests indicated favorable results, decreasing the percentage of errors from 66.7% in the first pre-test to 33.4% in the last post-test. We conclude, hence, that the valuation of the previous knowledge of the student, allied to a planned activity and the mastery of the teacher about the linguistic processes are essential for the construction of a productive and consistent knowledge.